Portable traffic monitoring device - Teoh, Chia Jie (Nanyang Technological University, 2024)
This project outlines the development of a portable traffic monitoring system utilizing Raspberry Pi and Oak D Lite camera technology. The system's objective is to contribute to traffic monitoring with wireless and autonomous functionality, minimizing human intervention. Throughout the project's phases, including testing, algorithm refinement, and casing design, notable progress has been achieved. Emphasis has been placed on enhancing system portability, improving data presentation clarity, and optimizing overall efficiency. While significant strides have been made in improving system accuracy, efficiency, and functionality, ongoing challenges and areas for improvement remain. Moving forward, efforts will focus on addressing power supply issues and enhancing tracking accuracy. The ultimate goal is to establish a comprehensive vehicle monitoring system accessible remotely, with potential applications in traffic transport and urban planning. In summary, while progress has been made, there are still imperfections which needed to be addressed in the future, for transforming the system into a potential useful tool in urban traffic monitoring.